2016
DOI: 10.1038/mp.2016.107
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting educational achievement from DNA

Abstract: A genome-wide polygenic score (GPS), derived from a 2013 genome-wide association study (N=127,000), explained 2% of the variance in total years of education (EduYears). In a follow-up study (N=329,000), a new EduYears GPS explains up to 4%. Here, we tested the association between this latest EduYears GPS and educational achievement scores at ages 7, 12 and 16 in an independent sample of 5825 UK individuals. We found that EduYears GPS explained greater amounts of variance in educational achievement over time, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
180
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(195 citation statements)
references
References 34 publications
11
180
1
3
Order By: Relevance
“…The latest GWAS was carried out on a sample of >293,000 individuals (Okbay et al, 2016) and produced 74 independent ("LD-free") hits. A replication of this study found that the polygenic score predicted 9% of the individual variance in educational achievement at age 16 (Selzam et al, 2016). Population differences in allele frequencies are normally correlated to phenotypic differences.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…The latest GWAS was carried out on a sample of >293,000 individuals (Okbay et al, 2016) and produced 74 independent ("LD-free") hits. A replication of this study found that the polygenic score predicted 9% of the individual variance in educational achievement at age 16 (Selzam et al, 2016). Population differences in allele frequencies are normally correlated to phenotypic differences.…”
Section: Introductionmentioning
confidence: 51%
“…Moreover, the GWAS hits identified by the three educational GWAS also predict general cognitive ability in their samples (Rietveld et al, 2013;Okbay et al, 2016). A reanalysis of the Okbay et al dataset revealed that the polygenic score also predicts general intelligence (3.6%) compared to 2% for the 2013 polygenic score (Selzam et al, 2016). Populationlevel polygenic scores (the average population frequency of alleles with a positive GWAS Beta) will be calculated to test the prediction that they explain variance in population IQ.…”
Section: Introductionmentioning
confidence: 99%
“…A recently introduced Genome-wide Polygenic Scoring (GPS) technique allows for thousands of genotyped markers in a person's DNA to be aggregated together to predict different traits. For example, in a recent study using this method, DNA information alone could explain 10% of the variation in school achievement of high school students (Selzam et al, 2017). Further research using GPS is likely to achieve even greater predictive power in many domains (Spiliopoulou et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Home environment is also not independent of genetic effects, as parents shape environments in line with their own genetic predispositions. Recent molecular genetics research has provided support for this, finding that DNA variants that contribute to differences in academic achievement also explain some of the variance in family SES (Selzam et al, 2016).…”
mentioning
confidence: 96%